2018
DOI: 10.1186/s12916-017-1000-8
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and health: an umbrella review of health outcomes and biological mechanisms of action

Abstract: BackgroundOur aims were to evaluate critically the evidence from systematic reviews as well as narrative reviews of the effects of melatonin (MLT) on health and to identify the potential mechanisms of action involved.MethodsAn umbrella review of the evidence across systematic reviews and narrative reviews of endogenous and exogenous (supplementation) MLT was undertaken. The Oxman checklist for assessing the methodological quality of the included systematic reviews was utilised. The following databases were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 165 publications
2
53
0
6
Order By: Relevance
“…Its secretion exhibits diurnal variation: it is low during the day since the pineal melatonin production is powerfully suppressed by light exposure. During the night, melatonin concentrations increase several times with a peak in the middle of the night (9). Several studies revealed that a proportion of individuals with ASD have lower levels of melatonin (5), as well as that deviations in biorhythm of melatonin secretion were observed (6).…”
Section: Introductionmentioning
confidence: 99%
“…Its secretion exhibits diurnal variation: it is low during the day since the pineal melatonin production is powerfully suppressed by light exposure. During the night, melatonin concentrations increase several times with a peak in the middle of the night (9). Several studies revealed that a proportion of individuals with ASD have lower levels of melatonin (5), as well as that deviations in biorhythm of melatonin secretion were observed (6).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine acts through the A 1 AR and A 2A AR in the brain, to promote sleep. Melatonin receptors are involved in regulation of circadian rhythm and the sleep cycle, based partly on larval exposure to 3 and 18 (50 and 30 µM, respectively) [104]. Gandhi et al [105] found that melatonin 60 promotes sleep in part through Ars, using A 2A AR KO mice and ADK inhibition with ABT-702 18.…”
Section: Pain Antidepressant Sleep and Other Behavioral Interventionmentioning
confidence: 99%
“…Adenosine acts through the A1AR and A2AAR in the brain to promote sleep. Melatonin receptors are involved in regulation of circadian rhythm and the sleep cycle (Posadzki et al, 2018). Gandhi et al (2015) found that melatonin 60 promotes sleep in part through ARs using A2AAR KO mice and ADK inhibition with ABT-702 18.…”
Section: Pain Antidepressant Sleep and Other Behavioral Interventionmentioning
confidence: 99%